(untitled) (Principles of Medical Toxicology, 2025)
Author Mr. Gourab Saha, Associate Professor, Department of Pharmaceutics, College of Pharmaceutical Sciences, Berhampur, Mohada, Odisha, India Abstract Accurate diagnosis of toxic exposures requires a systematic approach combining thorough clinical assessment with appropriate laboratory investigations. The diagnostic process begins with a detailed history addressing the substance involved, time of exposure, quantity, route, and intent, while recognizing challenges like altered mental status or intentional deception. Physical examination focuses on vital signs, pupil size, mucous membrane appearance, skin findings, and neurological status, with special attention to characteristic toxidromes that suggest specific poisonings. Laboratory testing includes both routine tests (electrolytes, glucose, renal and liver function, arterial blood gases) and toxin-specific assays. Toxicological screening employs immunoassays for rapid detection of common substances, though these have important limitations including cross-reactivity and false results. Definitive testing uses sophisticated analytical methods including gas and liquid chromatography, mass spectrometry, and specialized techniques for metals and other toxins. Interpretation requires understanding detection windows, metabolites, specimen selection, and confirmation thresholds. Integration of clinical findings with appropriate laboratory investigations remains essential, as testing must be guided by the clinical presentation rather than performed indiscriminately, with recognition that absence of a substance on screening does not exclude significant toxicity from agents not included in standard panels. Keywords: Toxicology Screening, Toxidromes, Analytical Methods, Chromatography, Mass Spectrometry, Clinical Assessment VIEW PDF